2007
DOI: 10.5194/os-3-451-2007
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of phytoplankton fluorescence in relation to the Straits of Messina (Sicily) tidal upwelling

Abstract: Abstract. In the Straits of Messina, large gradients of tidal displacements, as well as the topographic constrictions, determine the upwelling of deeper waters in the surface layer. This work describes the seasonal variability in the surface distribution of phytoplankton biomass depending on the upwelling phenomena. Temperature, salinity, nitrates and phytoplankton fluorescence were measured in 1994 and 1995 by continuous underway surface real-time measurements onboard dedicated research boats. Each survey was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The Menai Straits is affected by much less hydrocarbon pollution, as shipping activity is generally very low. Average sea surface water temperatures range from winter minimum temperatures of 3–5 °C and summer maximum temperatures of 17 °C for the Helgoland and Bangor sites and between 15 and 27 °C at the Messina site (El Hag & Fogg, ; Wiltshire & Manly, ; Azzaro et al ., ).…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The Menai Straits is affected by much less hydrocarbon pollution, as shipping activity is generally very low. Average sea surface water temperatures range from winter minimum temperatures of 3–5 °C and summer maximum temperatures of 17 °C for the Helgoland and Bangor sites and between 15 and 27 °C at the Messina site (El Hag & Fogg, ; Wiltshire & Manly, ; Azzaro et al ., ).…”
Section: Methodsmentioning
confidence: 92%
“…Prior studies of all three sites have shown spring blooms of phytoplankton in April/May for Helgoland and Messina (Gillbrich, ; Azzaro et al ., ) and in May/June for Bangor (Rodrigues & Williams, ). Concentrations of nutrients such as nitrate, phosphate and ammonium are subject to strong annual variations, which are only documented for the Helgoland site (Wiltshire et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, local strong and periodical upwelling processes, (e.g. [ 18 ]), bring deep-water to surface layers which may also facilitate the transport of egg/larvae between the two Mediterranean basins [ 107 ]. The exchange of only a limited number of migrant across the Strait of Sicily and/or Messina may be enough to prevent genetic differentiation between the Western and Eastern Mediterranean populations.…”
Section: Discussionmentioning
confidence: 99%
“…The Strait of Sicily is located between the island of Sicily and Tunisia and has approximately 360–430 m depth. The strait of Messina, located between the eastern tip of Sicily Island and mainland Italy, is a very narrow sill shallower than the strait of Sicily (3.1 km wide and approximately 80 m deep at the narrowest part [ 18 ]). Concerning oceanographic processes, the Almeria-Oran front (AOF) found between Spain and Algeria is one of the most studied dynamic systems acting as a barrier to gene flow in the Mediterranean (reviewed by [ 12 ]).…”
Section: Introductionmentioning
confidence: 99%
“…We also cite for completeness that the Strait of Messina (between Sicily and Italy, see Figure 1) is also affected by tide-induced upwelling (Hopkins et al 1984;Bignami & Salusti 1990;Androsov et al 1993) that is not detectable by means of wind records, and that this phenomenon is to be considered just as important as wind-induced upwelling, e.g. in the biological sense (Azzaro & Decembrini 2007).…”
Section: Wind Upwelling Index: Rmn Stationsmentioning
confidence: 92%